2008
DOI: 10.1021/ja8076846
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reaction of Fullerene C70 Encapsulating Two Molecules of H2

Abstract: New endohedral fullerene C(70) encapsulating one and two H(2) molecule(s) has been synthesized by organic reactions, the so-called "molecular surgery" method, and the first organic derivatization of H(2)@C(70) and (H(2))(2)@C(70) has been conducted. Although the interaction between inner H(2) and outer C(70) is rather weak, (H(2))(2)@C(70) exhibits smaller equilibrium constants in the Diels-Alder reaction with 9,10-dimethylanthracene than those of H(2)@C(70).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
123
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 129 publications
(136 citation statements)
references
References 16 publications
7
123
0
Order By: Relevance
“…Furthermore, the preparation of (H 2 ) 2 @C 70 [55] presages the availability of whole families of endofullerenes encapsulating several small molecules. We list below some ways that these materials might be used to prepare and study nuclear spin isomers.…”
Section: Future Directionsmentioning
confidence: 99%
“…Furthermore, the preparation of (H 2 ) 2 @C 70 [55] presages the availability of whole families of endofullerenes encapsulating several small molecules. We list below some ways that these materials might be used to prepare and study nuclear spin isomers.…”
Section: Future Directionsmentioning
confidence: 99%
“…In addition to the increasing literature on the chemical principles [5,6,7,8,9,10,11,12], spectroscopic investigations using infra-red (IR) [3,13,14,15], inelastic neutron scattering (INS) [3,16,17] and nuclear magnetic resonance (NMR) [3,18,19] have probed the physical characteristics of these complexes. Also, heat capacity measurements have identified a small splitting of the rotational line associated with the symmetry of the crystal field, a first indication of inter-fullerene contributions to the effective cage potential [20].…”
Section: Introductionmentioning
confidence: 99%
“…1 The dihydrogen and water endofullerenes H 2 @C 60 , H 2 O@C 60 , and their isotopologues, have been synthesized by the procedure known as 'molecular surgery', in which synthetic operations are used to open a hole in the fullerene allowing encapsulation of the guest, followed by a suturing technique to reform the pristine fullerene shell. [2][3][4] Recently the approach has been extended to C 70 and C 59 N. [5][6][7] The confined molecules display quantization of their coupled translational and rotational degrees of freedom, and exhibit phenomena such as nuclear spin isomerism and orthopara conversion. [8][9][10][11][12] Recently it was shown that nuclear spin conversion of the encapsulated water molecules in H 2 O@C 60 leads to a change in the dielectric constant of the material.…”
mentioning
confidence: 99%